Maternal, placental, and fetal distribution of titanium after repeated titanium dioxide nanoparticle inhalation through pregnancy. (April 2022) - D'Errico, J.N.; Doherty, C.; Reyes George, J.J.; Buckley, B.; Stapleton, P.A.
Abstract: Epidemiological studies have associated ambient engineered nanomaterials or ultrafine particulate matter (PM0.1 ), collectively referred to as nanoparticles (NPs), with adverse pregnancy outcomes including miscarriage, preterm labor, and fetal growth restriction. Evidence from non-pregnant models demonstrate that NPs can cross the lung air-blood barrier and circulate systemically. Therefore, inhalation of NPs during pregnancy leading to fetoplacental exposure has garnered attention. The purpose of this study was to evaluate the distribution of inhaled titanium dioxide nanoparticles (nano-TiO2 ) from the maternal lung to maternal and fetal systemic tissues. Pregnant Sprague Dawley rats were administered whole-body exposure to filtered air or of nano-TiO2 aerosols (9.96 ± 0.06 mg/m 3 ) between gestational day (GD) 4 and 19. On GD 20 maternal, placental, and fetal tissues were harvested then digested for ICP-MS analysis to measure concentrations of titanium (Ti). TEM was used to visualize particle internalization by the placental syncytium. The results demonstrate the extrapulmonary distribution of Ti to various maternal organs during pregnancy. Our study found Ti accumulation in the decidua/junctional and labyrinth zones of placentas embedded in all sections of uterine horns. Further, NPs deposited in the placenta, identified by TEM, were found intracellularly within nuclear, endoplasmic reticulum, and vesicle organelles. This study identified the systemic distribution and placental accumulation of Ti after nano-TiO2 aerosol inhalation in a pregnancy model. These findings arouse concerns for poor air quality for pregnant women and possible contributions to adverse pregnancy outcomes. Highlights: Inhaled nanoparticle aerosols distribute to maternal, placenta, and fetal tissues. Tissue accumulation is differentially deposited based on maternal inhalation or ingestion exposure routes. Nanoparticles are internalized by placental syncytial trophoblasts.